2018
DOI: 10.3390/mi9090424
|View full text |Cite
|
Sign up to set email alerts
|

Development, Modeling, Fabrication, and Characterization of a Magnetic, Micro-Spring-Suspended System for the Safe Electrical Interconnection of Neural Implants

Abstract: The development of innovative tools for neuroscientific research is based on in vivo tests typically applied to small animals. Most often, the interfacing of neural probes relies on commercially available connector systems which are difficult to handle during connection, particularly when freely behaving animals are involved. Furthermore, the connectors often exert high mechanical forces during plugging and unplugging, potentially damaging the fragile bone structure. In order to facilitate connector usage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
(42 reference statements)
1
4
0
Order By: Relevance
“…One magnetic connector for microelectrode arrays required up to 4.9 N for disconnection, which our design is significantly below (Shah et al, 2014). Another has disconnection forces in the several hundred mN range, which is comparable to our device (Hoch et al, 2018). Thus, it can be concluded that external leads can be connected and disconnected from our device with safe levels of force exerted on the mouse.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…One magnetic connector for microelectrode arrays required up to 4.9 N for disconnection, which our design is significantly below (Shah et al, 2014). Another has disconnection forces in the several hundred mN range, which is comparable to our device (Hoch et al, 2018). Thus, it can be concluded that external leads can be connected and disconnected from our device with safe levels of force exerted on the mouse.…”
Section: Resultssupporting
confidence: 74%
“…Based on existing designs, these are acceptable disconnection/connection force ranges. The commercially available Omnetics Nano Series connectors commonly used for this application require up to 2 N per contact (Hoch et al, 2018). Our design does not exceed this force, with most tested samples falling well below this value.…”
Section: Resultsmentioning
confidence: 99%
“…Medical monitoring is transforming from bulky stationary hospital machines into small‐sized wearable devices for personalized diagnostics, with lifestyle products such as fitness‐/activity trackers already on the market . Such gadgets are designed for checking specific body functions, with 24 h monitoring being most insightful, yet difficult to realize .…”
mentioning
confidence: 99%
“…Yet, magnetic links are already well established in commercial or industrial applications, albeit limited to rigid devices. They are, for instance, used as power connectors in consumer laptops, being entirely rigid, as well as in the assembly of soft robots, microfluidic devices, and now also enter the field of medical electronic systems . Furthermore, the utilization of liquid metals with both electrical and magnetic properties, although still in early stages, poses a promising route of incorporating magnetic connections into stretchable devices .…”
mentioning
confidence: 99%
“…By combining scalable 3D design and high-density recording sites, this fabrication approach may enable new classes of devices capable of large-scale neural recording to elucidate the functional connectivity of the brain. Hoch et al [18] address the problem associated with neural probe connector failure, which is triggered by excessive forces generated by repeated plugging/unplugging between recording sessions. They developed a new magnetic connector system that uses multiple magnet pairs and spring-suspended electrical contact pads realized using micro-electromechanical systems technologies to achieve reliable self-alignment of the connector parts at ±50 µm with negligible connection forces.…”
mentioning
confidence: 99%